Comparative study of manual liquid-based cytology (MLBC) technique and direct smear technique (conventional) on fine-needle cytology/fine-needle aspiration cytology samples - Pawar, Prajkta Suresh (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Liquid-based cytology technique enables cells to be suspended in a liquid medium and spread in a monolayer, making better morphological assessment. Automated techniques have been widely used, but limited due to cost and availability. AIM: The aim was to establish manual liquid-based cytology (MLBC) technique on fine-needle aspiration cytology (FNAC) material and compare its results with conventional technique. MATERIALS AND METHODS: In this study, we examined cells trapped in needles hub used for the collection of FNAC samples. 50 cases were examined by the MLBC technique and compared with the conventional FNAC technique. By centrifugation, sediment was obtained and imprint was taken on defined area. Papanicolaou (Pap) and May-Grünwald Giemsa (MGG) staining was done. Direct smears and MLBC smears were compared for cellularity, background, cellular preservation, and nuclear preservation. Slides were diagnosed independently by two cytologists with more than 5 years’ experience. Standard error of proportion was used for statistical analysis. RESULTS: Cellularity was low in MLBC as compared with conventional smears, which is expected as remnant material in the needle hub was used. Nuclei overlap to a lesser extent and hemorrhage and necrosis was reduced, so cell morphology can be better studied in the MLBC technique. P value obtained was <0.05. CONCLUSION: This MLBC technique gives results comparable to the conventional technique with better morphology. In a set up where aspirators are learners, this technique will ensure adequacy due to remnant in needle hub getting processed